Modeling fracture in elasto-plastic solids by embedded-discontinuity stress-hybrid finite element formulation. Issue 5 (18th February 2022) - Dujc, Jaka; Brank, Boštjan
Abstract: The Hellinger-Reissner principle is applied to derive a hybrid-mixed quadrilateral finite element with embedded-discontinuity in displacements, which can model a discrete crack (interface) within the element, and its sliding (and opening). The chosen material models are elasto-plasticity with hardening for the bulk, and traction-separation plasticity with softening for the interface. The latter model describes localized material failure and relates cohesion degradation with the fracture energy. The fulfillment of the inelastic relations at the bulk's integration points is performed by a stress-driven update algorithm. The stress and embedded-discontinuity kinematic parameters are condensed on the element level, allowing for an efficient implementation.